Pengaruh Penambahan Infusa Kapulaga (Amomum Cardamomum) Pada Kefir Susu Sapi Terhadap Nilai Ph, Kadar Air, Total Padatan Dan Properti Fisik - Hilman, Hilman Fathul Hakim; Novia, Novia Rahayu; putri, Putri Dian Wulansari (Bulletin of Applied Animal Research, 2021)
This study aims to determine the effect of adding cardamom infusion as a natural antibacterial with cow's milk kefir in terms of chemical characteristics and physical properties. Parameters measured on chemical characteristics include pH value, water content, and total solids. For physical properties, the parameters measured were color, aroma, taste, and texture. This type of research was experimental with a completely randomized design (CRD) method with four treatments and six replications, with cardamom infusion concentrations of 5%, 10% and 15%. The results showed that the addition of cardamom infusion to cow's milk kefir had an effect on the pH value, with samples without the addition of cardamom infusion having a pH value of 4.68 while the kefir added with cardamom infusion of 5%, 10% and 15% had values ​​exceeding the standard. On the water content and total solids, the addition of cardamom infusion had an effect with an average of 88.79% and 11.20%, respectively. The addition of cardamom infusion to kefir affects the color, aroma, taste and texture, namely the higher the concentration of cardamom infusion given, the more brownish white the color of kefir, the more cardamom-flavored aroma, and the thicker the texture. Keywords: kefir, cardamom, pH, water content, total solids